Investigation of the Basic Dimensional Properties and Biomechanical Performance of Artificial ACL Grafts Produced by 3-D Braiding Method - Omer Fırat Tursucular (Textile & Leather Review, 2024)
In the current study, an investigation of basic dimensional properties and biomechanical performance of artificial ACL grafts produced by the 3-D braiding method was carried out. Artificial ACL grafts were produced using the 3-D braiding process. All 3-D braiding grafts were produced using various technical yarns for raw and bio-finishing grafts. Ethylene oxide (EtO) sterilization was applied to all grafts. The effects of yarn types, yarn counts, and 3-D braiding constructions on EtO sterilized raw and bio-finished artificial ACL grafts were examined. In conclusion; the tensile strength and thickness values of all 3-D braiding structured ACL grafts were suitable for artificial ligament grafts. Additionally, its grammage values were extremely light. The yarn type, yarn count, and 3-D braiding construction were the most effective process parameters on thickness, grammage, and tensile strength values. They can be improved by using x2-layered 3-D braiding structures, thicker yarn counts, and more than 1 core yarn in similar studies to be conducted in the future.